Graveyard shift - Sugar, Larry; Singleton, Ralph S. (Ralph Stuart), 1940-; Andrews, David, 1952-; Wolf, Kelly; Macht, Stephen; Dourif, Brad, 1950-; King, Stephen, 1947-; Paramount Pictures Corporation (1914-1927); Paramount Home Video (Firm) (Hollywood, Calif. : Paramount Home Video, 2002)
When an abandoned textile mill is reopened, several employees meet mysterious deaths during the graveyard shift. The sadistic foreman chooses a group to clean up the rat-infested basement. But what the workers find is a maze of tunnels leading to the cemetery, and an unimaginable horror that comes alive in the dead of night.
Based on the short story "Graveyard shift" by Stephen King.
Videodisc release of the 1990 motion picture.
Music, Anthony Marinelli and Brian Banks ; exec. producers, Bonnie and Larry Sugar ; screenplay, John Esposito ; producers, William J. Dunn and Ralph S. Singleton ; director, Ralph S. Singleton.
David Andrews, Kelly Wolf, Stephen Macht, and Brad Dourif.
Rated R.
DVD, region 1, widescreen presentation, enhanced for 16:9 TVs; Dolby Digital, NTSC.
Keywords: Textile industry -- Accidents -- Drama; Murder -- Drama; Cemeteries -- Drama; Cemeteries; Murder; Textile industry -- Accidents; Horror films; Feature films; Horror films; Horror -- Feature; Drama; Feature films; Horror films